Prediction of lifetime milk production from early lactation traits in Hariana cattle - DALAL, D S; MALIK, Z S; CHHIKARA, B S; CHANDER, RAMESH (The Indian Journal of Animal Sciences, 2014)
The data on early lactation production, reproduction and production efficiency trailS of Hariana cows (372) maintained at Government Livestock Farm, Hisar, Haryana, from 1976 to 1996 were used to predict lifetime milk production up to third (LTP-3) and fifth (LTP-5) lactations. Prediction of LTP-3 and LTP-5 was attempted by fitting multiple linear regression models using Backward Elimination Procedure. In set, I, consisting on out of 7 traits (first lactation), the best equation under multiple regression model explained 61.00% of variability in LTP-3. The best equation under set-II containing 7 out of II first and second factation traits showed 91.25% of variaoility in LTP-3 ana t6e best equation containing 3 (FLL, FLMY and SLMY) out of II first and second lactation traits explained 61.62% variability in LTP-5. When only production efficiency traits were incorporated in the prediction equation then the best equations having 3 out of 6 production efficiency traits explained 67.61 and 47.65% variation in LTP-3 and LTP-5 respectively. The optimum equations Linder set-IV including 6 out of 17 traits for LTP-3 and 4 out of 17 traits for LiP-5 explained 41.33 and 61.81 % variation in LTP-3 and LTP-5, respectively. From the results it may be concluded that early lactation production and reproduction traits were more effective to predict lifetime milk production as compared to production efficiency traits alone.